Cardiovascular Outcomes According to Systolic Blood Pressure in Patients With and Without Diabetes: An ACCOMPLISH Substudy - Weber, Michael A. (J Clin Hypertens (Greenwich), 2016)
To evaluate the effects of achieved systolic blood pressure (SBP) during treatment on cardiovascular (CV) outcomes, the authors measured event rates of a composite primary endpoint (CV death or nonfatal myocardial infarction or stroke) at on‐treatment SBPs of ≥140 mm Hg and the 10 mm Hg intervals of <140 mm Hg, <130 mm Hg, and <120 mm Hg in 6459 patients with diabetes (mean age, 67) and 4246 patients without diabetes (mean age, 69) from the Avoiding Cardiovascular Events in Combination Therapy in Patients Living With Systolic Hypertension (ACCOMPLISH) trial. In the diabetic cohort, the primary endpoint was 49% lower (P<.001) at <140 mm Hg than at ≥140 mm Hg, and the separate components of this endpoint were also significantly reduced. Further SBP reductions did not improve outcomes, and at <120 mm Hg they were no longer different (except for stroke) from ≥140 mm Hg. In contrast, in the nondiabetic cohort, the primary endpoint event rate fell steadily (although not significantly) through the decreasing SBP categories until it was reduced by 45% (P=.0413) at <120 mm Hg. Total stroke rates for both the diabetic (−56%, P=.0120) and nondiabetic (−68%, P=.0067) cohorts were lowest at <120 mm Hg, and adverse renal events (serum creatinine increase ≥50%) were significantly lowest in the range of 130 mm Hg to 139 mm Hg for both cohorts. Diabetic patients (<140 mm Hg or <130 mm Hg) and nondiabetic patients (<120 mm Hg) may require different SBP targets for optimal CV protection, although stroke and renal considerations should also influence the selection of blood pressure targets.